2022
DOI: 10.3390/nu14061297
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Alcohol Intake to Kidney Function and Mortality Observational, Population-Based, Cohort Study

Abstract: Data are conflicting about the effects of alcohol intake on kidney function. This population-based study investigated associations of alcohol intake with kidney function and mortality. The study cohort included adult participants in Exam-1, Exam-2 (6-year follow-up), and Exam-3 (20-year follow-up) of the Gubbio study. Kidney function was evaluated as estimated glomerular filtration rate (eGFR, CKD-Epi equation, mL/min × 1.73 m2). Daily habitual alcohol intake was assessed by questionnaires. Wine intake account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…Although the influence of modifiable factors is often regarded as limited, several studies have reported that dietary habits and other modifiable factors may modulate the decline of kidney function over time [5,6]. In agreement with those studies [5,6], a lower physical activity in leisure time, a lower alcohol intake, a higher protein intake, a higher sodium intake, and a lower potassium intake in the Gubbio study population associated with a greater kidney function, decline over time independently of each other [7][8][9][10]. The Gubbio study is a prospective, longitudinal project investigating cardiovascular disease, kidney disease, and other public health objectives in a sample of the general population residing in a city of north-central Italy [11,12].…”
Section: Introductionsupporting
confidence: 63%
“…Although the influence of modifiable factors is often regarded as limited, several studies have reported that dietary habits and other modifiable factors may modulate the decline of kidney function over time [5,6]. In agreement with those studies [5,6], a lower physical activity in leisure time, a lower alcohol intake, a higher protein intake, a higher sodium intake, and a lower potassium intake in the Gubbio study population associated with a greater kidney function, decline over time independently of each other [7][8][9][10]. The Gubbio study is a prospective, longitudinal project investigating cardiovascular disease, kidney disease, and other public health objectives in a sample of the general population residing in a city of north-central Italy [11,12].…”
Section: Introductionsupporting
confidence: 63%
“…Of the 34 publications selected, the present meta-analysis finally included 12 publications [ 19 , 20 , 21 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] from 11 cohort studies ( N = 14,634,940), including the Physicians’ Health Study (PHS) study which defined the outcome as eGFR of <55 mL/min [ 32 ]. We excluded 23 publications because two publications were cross-sectional studies [ 41 , 42 ], two did not assess alcohol consumption (g/day) as a predictor of proteinuria and/or low GFR [ 43 , 44 ], three categorized alcohol consumption into only two levels (none vs. ≥1 drink/day [ 45 ], no use vs. use of alcohol [ 46 ], and alcohol consumption of <20 vs. ≥20 g/day [ 47 ]), four did not stratify current drinkers by alcohol consumption level (g/day) [ 48 , 49 , 50 , 51 ], one had the highest alcohol consumption category with the lower boundary of <12 g/day, [ 52 ] one had a sex-specific definition of alcohol consumption level [ 53 ], one did not define the outcome of CKD [ 54 ], seven did not have the outcome of incidence of proteinuria or low GFR [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ], one had missing information on the number of participants of alcohol consumption categories [ 62 ], and one reported similar results in previous publications [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…While there are few reports on the impact of alcohol abuse on the prognosis of individuals with IMH, a recent systematic review determined that alcohol abuse is independently associated with arteriosclerosis, especially in men and older patients (30). As alcohol could also damage kidney function (31), it is believed that long-term alcohol abuse in elderly individuals might exacerbate damage to the kidneys and arteriosclerosis. This could increase the possibility of ULP formation, resulting in the poor prognosis of patients with IMH.…”
Section: Discussionmentioning
confidence: 99%